Integration of Relational and Graph Databases Functionally - Pokorný Jaroslav (Foundations of Computing and Decision Sciences, 2019)
In today’s multi-model database world there is an effort to integrate databases expressed in different data models. The aim of the article is to show possibilities of integration of relational and graph databases with the help of a functional data model and its formal language – a typed lambda calculus. We suppose the existence of a data schema both for the relational and graph database. In this approach, relations are considered as characteristic functions and property graphs as sets of single-valued and multivalued functions. Then it is possible to express a query over such integrated heterogeneous database by one query expression expressed in a version of the typed lambda calculus. A more user-friendly version of such language could serve as a powerful query tool in practice. We discuss also queries sent to the integrated system and translated into queries in SQL and Cypher - the graph query language for Neo4j.